RSK1 and RSK2 serine/threonine kinases regulate different transcription programs in cancer - Yang, Won Seok; Caliva, Maisel J.; Khadka, Vedbar S.; Tiirikainen, Maarit; Matter, Michelle L.; Deng, Youping; Ramos, Joe W. (Frontiers in Cell and Developmental Biology, 2023)
The 90 kDa ribosomal S6 kinases (RSKs) are serine threonine kinases comprising four isoforms. The isoforms can have overlapping functions in regulation of migration, invasion, proliferation, survival, and transcription in various cancer types. However, isoform specific differences in RSK1 versus RSK2 functions in gene regulation are not yet defined. Here, we delineate RSK isoform-specific transcriptional gene regulation by comparing transcription programs in RSK1 and RSK2 knockout cells using microarray analysis. Microarray analysis revealed significantly different mRNA expression patterns between RSK1 knockout and RSK2 knockout cell lines. Importantly some of these functions have not been previously recognized. Our analysis revealed RSK1 has specific roles in cell adhesion, cell cycle regulation and DNA replication and repair pathways, while RSK2 has specific roles in the immune response and interferon signaling pathways. We further validated that the identified gene sets significantly correlated with mRNA datasets from cancer patients. We examined the functional significance of the identified transcriptional programs using cell assays. In alignment with the microarray analysis, we found that RSK1 modulates the mRNA and protein expression of Fibronectin1, affecting cell adhesion and CDK2, affecting S-phase arrest in the cell cycle, and impairing DNA replication and repair. Under similar conditions, RSK2 showed increased ISG15 transcriptional expression, affecting the immune response pathway and cytokine expression. Collectively, our findings revealed the occurrence of RSK1 and RSK2 specific transcriptional regulation, defining separate functions of these closely related isoforms.